Self-Perceived Occupational Stress and Professional Well-Being of Local Government Employees - Madrid, Patrick (Azal Arts and Humanities, 2026)
Abstract Occupational stress and professional well-being significantly influence employee productivity, organizational efficiency, and public service delivery within local government institutions. This qualitative phenomenological study explored the self-perceived occupational stress and professional well-being experiences of local government employees in the Municipality of Delfin Albano, Isabela. Specifically, the study examined employees’ perceived sources of workplace stress, emotional and professional challenges, coping mechanisms, and perceptions of well-being within the local government work environment. Data were gathered through semi-structured in-depth interviews with twelve purposively selected local government employees from different municipal offices. Thematic analysis following Braun and Clarke’s framework was utilized in analyzing the data. Findings revealed that employees experienced occupational stress due to workload demands, administrative pressures, role multiplicity, public service expectations, time constraints, and workplace interpersonal dynamics. Participants also described challenges related to emotional exhaustion, work-life balance, and institutional pressures associated with public accountability and service delivery. Despite these challenges, employees demonstrated resilience through peer support, family support systems, spirituality, positive workplace relationships, and adaptive coping strategies. Participants further emphasized that supportive leadership, collaborative work environments, and professional recognition contributed positively to their professional well-being. The findings underscore the importance of workplace wellness initiatives, psychosocial support systems, and employee-centered organizational practices in promoting occupational well-being and sustainable public service performance. The study proposes a contextualized employee wellness and psychosocial support program for local government institutions. Keywords: occupational stress, professional well-being, local government employees, workplace stress, phenomenology, public service, employee wellness